ISU-ISU PENDIDIKAN GLOBAL - Ike Nilawati Rohaenah; Uus Ruswandi; Muhammad Erihardiana (Cross-border, 2020)
The importance of studying global education issues provides knowledge and skills about the world as a whole regarding diversity, ethnicity, culture. pluralism. The aim of global education is to develop the knowledge, skills, attitudes needed to live effectively in a world and tolerance, ethnic diversity, cultural pluralism and an increasing interdependence of mutual respect and respect. This research uses the book literacy method. Results obtained by global education can apply tolerance, mutual respect and respect, can live peacefully.